Aid and growth: Asymmetric effects? - Leo Dörr (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2024)
This paper provides new empirical findings on the aid-growth relation. We find evidence for considerable asymmetry in the aid-growth relation; i.e., aid cuts have a large negative impact on economic activity, while increasing aid may be ineffective in promoting growth. Development aid thus largely replaces rather than complements domestic resources. We innovate by combining dynamic generalized method of moments techniques with asymmetric effect analysis. Unlike previous studies in this area, our empirical design allows us to account for potential weak instrument problems and endogeneity concerns when estimating the effects of aid upturns and downturns separately.
Keywords: O11; O40; C33; 330; Aid effectiveness; economic growth; asymmetric effect analysis